Thickness-Tunable Self-Assembled Colloidal Nanoplatelet Films Enable Ultrathin Optical Gain Media - Erdem, Onur; Foroutan, Sina; Gheshlaghi, Negar; Guzelturk, Burak; Altintas, Yemliha; Demir, Hilmi Volkan (Amer Chemical Soc, 2020)
We propose and demonstrate construction of highly uniform, multilayered superstructures of CdSe/CdZnS core/shell colloidal nanoplatelets (NPLs) using liquid interface self-assembly. These NPLs are sequentially deposited onto a solid substrate into slabs having monolayer-precise thickness across tens of cm(2) areas. Because of near-unity surface coverage and excellent uniformity, amplified spontaneous emission (ASE) is observed from an uncharacteristically thin film having 6 NPL layers, corresponding to a mere 42 nm thickness. Furthermore, systematic studies on optical gain of these NPL superstructures having thicknesses ranging from 6 to 15 layers revealed the gradual reduction in gain threshold with increasing number of layers, along with a continuous spectral shift of the ASE peak (similar to 18 nm). These observations can be explained by the change in the optical mode confinement factor with the NPL waveguide thickness and propagation wavelength. This bottom-up construction technique for thickness-tunable, three-dimensional NPL superstructures can be used for large-area device fabrication.
Demir, Hilmi Volkan/0000-0003-1793-112X; Erdem, Onur/0000-0003-2212-965X; Foroutan Barenji, Sina/0000-0003-0623-8987;
Keywords: Liquid Interface Self-Assembly; Colloidal Nanoplatelets; Planar Waveguides; Optical Gain; Amplified Spontaneous Emission